RADICAL RETROPUBIC PROSTATECTOMY: THE FIRST RUSSIAN EXPERIENCE OF 15-YEAR FOLLOW-UP AFTER SURGERY - E. I. Veliev (Onkourologiâ, 2014)
The results of the maximum of more than 15 years of follow-up of Russia’s first large series of patients after radical retropubic prostatectomy (RPE) were traced. The data of 1367 patients who had undergone RPE at the Clinic of Urology, S.P. Kirov Military Medical Academy, in 1997 to 2003 and at the Clinic of Urology, Russian Medical Academy of Postgraduate Education, in 2001 to 2010 were retrospectively studied. After excluding 626 patients who had an incomplete set of preoperative/postoperative characteristics, a postoperative follow-up of < 6 months, neoadjuvant hormonal or radiation therapy, the trial included 741 patients. Their median age at surgery was 64 years (interquartile range (IQR): 59-68); median prostatespecific antigen (PSA), 8.7 ng/ml (IQR: 6.2-14); median follow-up, 65 months (IQR: 50-87; the maximum follow-up period, 189 months). Out of the 741 patients, 30.2, 28.3, and 41.5% were referred to as D’Amico classification low-, moderate-, and high-risk groups, respectively. Five-, 10-, and 15-year relapse-free survival rates were 80.3, 74.7, and 66.7%; 5-, 10-, and 15-year cancer-specific survival rates were 98.3, 95.9, and 85.7%; and 5-, 10-, and 15-year overall survival rates were 92.5, 81.4, and 64.3%, respectively. The significant predictors of biochemical recurrence were a preoperative PSA level of 10.1–20 ng/ml (p = 0.041), > 20 ng/ml (p = 0.003); pathological stage pT3b–4N0 (p = 0.006) and any stage pT N1 (p = 0.003). Further investigations are needed to identify groups of patients who will have the most benefit from surgery.